2015
DOI: 10.1016/j.jmpt.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes for Neurogenic Claudication Using a Multimodal Program for Lumbar Spinal Stenosis: A Retrospective Study

Abstract: This study showed preliminary evidence for improved outcomes in patients with neurogenic claudication participating in a 6-week nonsurgical multimodal Boot Camp Program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
(42 reference statements)
0
12
0
1
Order By: Relevance
“…Treatment options for neurogenic claudication include manipulation, active and passive physical therapies, medication, epidural steroid injections, and decompression surgery [ 1 ]. The evidence for chiropractic treatment options is sparse [ 1 , 11 14 ]. However several studies have found that a combination of manual care methods, most often including flexion distraction and sciatic nerve mobilization, have been effective in reducing patient reported disability [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options for neurogenic claudication include manipulation, active and passive physical therapies, medication, epidural steroid injections, and decompression surgery [ 1 ]. The evidence for chiropractic treatment options is sparse [ 1 , 11 14 ]. However several studies have found that a combination of manual care methods, most often including flexion distraction and sciatic nerve mobilization, have been effective in reducing patient reported disability [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for chiropractic treatment options is sparse [ 1 , 11 14 ]. However several studies have found that a combination of manual care methods, most often including flexion distraction and sciatic nerve mobilization, have been effective in reducing patient reported disability [ 11 14 ]. Ammendolia and Chow conducted a preliminary study incorporating a conservative multimodal treatment method with 49 patients, which demonstrated promising outcomes for neurogenic claudication [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…45 Radicular pain is defined as ectopic nociceptive firing within spinal nerves due to inflammation, mechanical strain, or possible ischemic damage to dorsal root ganglia, resulting in pain perceived in the nerve-supplied territory. 45 Interventions: Education about the condition 13,[25][26][27][28][29]33,34 Neurodynamics (neural mobilization) when tolerated 46 Spinal manipulation (thrust and/or nonthrust as tolerated) 10,14,16,39,47 Directional preference exercises 42 Neurogenic claudication: pain caused by intermittent compression and/or ischemia of a single or multiple nerve roots 48 Interventions: Education about the condition 13,[25][26][27][28][29]33,34 Spinal manipulation (thrust and/or nonthrust as tolerated) [49][50][51] Neurodynamics (neural mobilization) [49][50][51] Muscle stretching 49,51 Lumbar mobilization exercise 49,51 Self-management via a cognitive behavioral approach including goal-setting, graded activity, pacing, relaxation, and body positioning techniques to reduce lumbar lordosis 49,51 Home exercises when tolerated 49,51 Comanage with other providers when needed 52 Central sensitization...…”
Section: Consensus Statements: 6 Components Of Multimodal Chiropractimentioning
confidence: 99%
“…We have designed and implemented a training program for LSS known as the Boot Camp Program for LSS [ 24 ]. This program aims to address the multi-faceted aspects of LSS using a multi-modal non-surgical approach with a focus on self-management and the goals of improved walking ability, overall functional status and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous retrospective study we evaluated 49 consecutive patients who completed the Boot Camp Program and assessed the difference in self-report outcomes selected a priori [ 24 ]. Outcome measures included the Oswestry Low Back Pain Disability Index, the walking score of the Oswestry Low Back Pain Disability Index, the three subscales of the Zurich Swiss Spinal Questionnaire, and the Numeric Rating Scale for leg and back pain.…”
Section: Introductionmentioning
confidence: 99%